English as a contact language - Schreier, Daniel, 1971-; Hundt, Marianne (Cambridge : Cambridge University Press, 2013)
'Recent developments in contact linguistics suggest considerable overlap of branches such as historical linguistics, variationist sociolinguistics, pidgin/creole linguistics, language acquisition, etc. This book highlights the complexity of contact-induced language change throughout the history of English by bringing together cutting-edge research from these fields. Special focus is on recent debates surrounding substratal influence in earlier forms of English (particularly Celtic influence in Old English), on language shift processes (the formation of Irish and overseas varieties) but also on dialects in contact, the contact origins of Standard English, the notion of new epicentres in World English, the role of children and adults in language change as well as transfer and language learning. With contributions from leading experts, the book offers fresh and exciting perspectives for research and is at the same time an up-to-date overview of the state of the art in the respective fields'--
1. Introduction: nothing but a contact language... / Marianne Hundt and Daniel Schreier -- 2. The role of contact in English syntactic change in the Old and Middle English periods / Olga Fischer -- 3. Multilingualism and code-switching as mechanisms of contact-induced lexical change in late Middle English / Herbert Schendl -- 4. The contact origins of Standard English / Laura Wright -- 5. English as a contact language in the British Isles / Juhani Klemola -- 6. English as a contact language in Ireland and Scotland / Raymond Hickey -- 7. The contact dynamics of socioethnic varieties in North America / Walt Wolfram-- 8. English as a contact language: the'New Englishes' / Edgar W. Schneider -- 9. English as a contact language: lesser-known varieties / Daniel Schreier -- 10. The role of mundane mobility and contact in dialect death and dialect birth / David Britain -- 11. The diversification of English: old, new and emerging epicenters / Marianne Hundt -- 12. Driving forces in English contact linguistics / Salikoko S. Mufwene -- 13. Substrate influence and universals in the emergence of contact Englishes: re-evaluating the evidence / Donald Winford -- 14. Transfer and contact in migrant and multiethnic communities: the conversational historical be + -ing present in South African Indian English / Rajend Mesthrie -- 15. English as a contact language: the role of children and adolescents / Paul Kerswill, Jenny Cheshire, Sue Fox and Eivind Torgersen -- 16. Innovation and contact: the role of adults (and children) / Sarah G. Thomason -- 17. Accelerator or inhibitor? On the role of substrate influence in interlanguage development / Terence Odlin -- 18. Speculating on the future of English as a contact language / Christian Mair.
Includes bibliographical references (p. 329-384) and index.
Keywords: English language -- History; English language -- Variation; English language -- Standardization; Languages in contact; Historical linguistics